RAG2's non-core domain contributes to the ordered regulation of V(D)J recombination - Curry, John D. (Oxford University Press, 2008)
Variable (diversity) joining [V(D)J] recombination of immune gene loci proceeds in an ordered manner with D to J portions recombining first and then an upstream V joins that recombinant. We present evidence that the non-core domain of recombination activating gene (RAG) protein 2 is involved in the regulation of recombinatorial order. In mice lacking the non-core domain of RAG2 the ordered rearrangement is disturbed and direct V to D rearrangements are 10- to 1000-times increased in tri-partite immune gene loci. Some forms of inter-chromosomal translocations between TCRβ and TCRδ D gene segments are also increased in the core RAG2 animals as compared with their wild-type (WT) counterparts. In addition, the concise use of proper recombination signal sequences (RSSs) appears to be disturbed in the core RAG2 mice as compared with WT RAG2 animals.